SOCIAL CONTRIBUTIONS OF HANS EYSENCK’S PSYCHOLOGY - Seoane, Julio (Anales de Psicología / Annals of Psychology)
The time of Eysenck can describe herself like a rich time in shades and in perspectives; without a doubt, from the 30’s at the 90’s, Europe lives in a packed period of social, political and scientific events. As all the intellectuals that deserved that name for then, Eysenck carries out its work in interaction with the social and political events of the moment. Hans Eysenck is one of the most fascinating representatives in the current psychological transition that evolves from a systematic psychology toward a practical and sectoral psychology. The analysis of their meaning and the interpretation of the psychological sense of its investigations is one of the most suggestive projects for the understanding of the current state and future of our discipline. Eysenck granted a great importance to the social aspects along all its work, to the margin that its perspective is debatable, politically incorrect or caused by its first years of education.